Characteristics of Cloud to Ground (CG) Lightning and Heavy Rainfall in Medan and Deli Serdang - Tarigan, Patra Mesiari; Humaidi, Syahrul; Darmawan, Yahya; Situmorang, Marhaposan; Rianna, Martha (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
The areas of Medan and Deli Serdang have complex topography, stretching from the slopes of Bukit Barisan Mountains to the east coast of North Sumatera. This condition causes Medan and Deli Serdang areas frequently form convective clouds that produce rain and lightning. This research utilizes Cloud to Ground (CG) lightning data and rainfall from 2019-2022 to analyse the characteristics and relationship between lightning and rainfall in Medan and Deli Serdang. CG lightning data is obtained from Lightning Detector equipment with a 10 km radius to avoid noise and obtain better data. Rainfall data above 50 mm/day (heavy rain) is used, which is obtained from 3 rain gauges locations. The study results showed that there was an increase in lightning events along with an increase of rainfall which showed almost the same pattern of peak activity from lightning and rainfall. The correlation between heavy rainfall and CG lightning, in the Medan and Deli Serdang areas are moderate positive, around r=0.566 for CG-, r=0.567 for CG+ and r= 0.576 for total CG. The highest correlation in Sunggal Rain Station is r = 0.947, in Deli Serdang Climatological Station is r = 0.950 and in the Kualanamu Meteorological Station is r = 0.932.